2021
DOI: 10.1371/journal.pone.0252635
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase 2 inhibition reduces serine-129 phosphorylation of physiological nuclear alpha-synuclein but not of the aggregated alpha-synuclein

Abstract: Accumulation of aggregated alpha-synuclein (α-syn) is believed to play a pivotal role in the pathophysiology of Parkinson’s disease (PD) and other synucleinopathies. As a key constituent of Lewy pathology, more than 90% of α-syn in Lewy bodies is phosphorylated at serine-129 (pS129) and hence, it is used extensively as a marker for α-syn pathology. However, the exact role of pS129 remains controversial and the kinase(s) responsible for the phosphorylation have yet to be determined. In this study, we investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Furthermore, treatment with a designed highly selective inhibitor for PLK2, compound 37, reduced α-synuclein phosphorylation in rat brain [ 108 , 109 ]. However, the inhibitor had no effect on α-synuclein aggregation, p-Ser129, or inter-neuronal spreading of the aggregated α-synuclein in the S129A preformed fibril injection model [ 110 ]. These findings suggest that PLK2 could be a potential target for the development of novel therapies, although further optimization is still required at the current stage ( Figure 4 ).…”
Section: Pathological Impact Of Phosphorylated Synuclein and Its Pote...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, treatment with a designed highly selective inhibitor for PLK2, compound 37, reduced α-synuclein phosphorylation in rat brain [ 108 , 109 ]. However, the inhibitor had no effect on α-synuclein aggregation, p-Ser129, or inter-neuronal spreading of the aggregated α-synuclein in the S129A preformed fibril injection model [ 110 ]. These findings suggest that PLK2 could be a potential target for the development of novel therapies, although further optimization is still required at the current stage ( Figure 4 ).…”
Section: Pathological Impact Of Phosphorylated Synuclein and Its Pote...mentioning
confidence: 99%
“… Schematic pathways of α-synuclein phosphorylation by kinases in the neurodegeneration process and potential pharmacotherapeutic targets [ 56 , 104 , 106 , 107 , 108 , 109 , 110 ]. NO: nitric oxide; NOS: NO synthase; ROS: reactive oxygen species; L-NNA: N(omega)-nitro-L-arginine, a competitive inhibitor of nitric oxide synthase; GRK: G-protein-coupled receptor kinase; CKII: casein kinase II; PLK: polo-like kinase; PPX: pramipexole.…”
Section: Figurementioning
confidence: 99%
“…Phosphorylation at Ser129 also regulates the inhibition of TH by α-Syn; PLK2 reduces its ability to inhibit TH or activate PP2A by phosphorylation of α-Syn ( 126 ). PLK2 mainly phosphorylates soluble α-Syn ( 151 ); Inhibition of PLK2 triggers autophagic elimination of α-Syn ( 152 ). Oxidative stress might play a key role in PLK2 phosphorylation of α-Syn, and antioxidant NAC could completely block iron-induced up-regulation of PLK2, CK2 and p-Ser129 α-Syn ( 140 ); However, as PLK2 induces elevation of α-Syn in copper-treated SHSY5Y neuroblastoma cells, both PP2A level and oxidative status remains unchanged ( 153 ).…”
Section: Role Of Plk2 In Diseasesmentioning
confidence: 99%
“…Wakamatsu et al also reported that nuclear aSyn is preferentially phosphorylated compared to cytosolic aSyn 50 . However, most of these studies were based on immunohisto-/cytochemistry and relied on the use of a single pS129 antibody [50][51][52][53][54] (Figure S1). Furthermore, the cross-reactivity of pS129 antibodies towards nuclear proteins has not been systematically assessed.…”
Section: All Ps129 Antibodies Cross-react With Several Nuclear Protei...mentioning
confidence: 99%